Altered Functional Network Associated With Cognitive Performance in Early Parkinson Disease Measured by Eigenvector Centrality Mapping - Cao, Fang; Guan, Xiaojun; Ma, Yanqing; Shao, Yuan; Zhong, Jianguo (Frontiers in Aging Neuroscience, 2020)
Objective: To investigate relationships between whole-brain functional changes and performance of multiple cognitive functions in early Parkinson Disease. Methods: In the current study, we evaluated resting-state functional MRI (rsfMRI) data and neuropsychological assessments for various cognitive functions in a cohort with 84 early PD patients from Parkinson's Progression Markers Initiative (PPMI). Eigenvector centrality (EC) mapping based on rsfMRI was used to identify the functional connectivity of brain areas correlated with different neuropsychological scores at a whole-brain level. Results: Our study demonstrated that in the early PD patients, scores of Letter Number Sequencing (Robbins et al.) were positively correlated with EC in the left inferior occipital gyrus and lingual gyrus. The immediate recall scores of Hopkins Verbal Learning Test-Revised (HVLT-R) were positively correlated with EC in the left superior frontal gyrus. No correlation was found between EC and other cognitive performance scores. Conclusions: Functional alternations in the left occipital lobe (inferior occipital and lingual gyrus) and left superior frontal gyrus may account for the performance of working memory and immediate recall memory respectively in early PD. These results may broaden the understanding of potential mechanism of cognitive impairments in early PD.